Reduction of mRNA m6A associates with glucose metabolism via YTHDC1 in human and mice. (April 2023) - Yang, Kun; Sun, Juan; Zhang, Zijie; Xiao, Mengyao; Ren, Decheng; Liu, Song-Mei
Abstract: Aims: N 6 -methyladenosine (m 6 A) in mRNA is involved in glucose metabolism. Our goal is to investigate the relationship of glucose metabolism, m 6 A and YTH domain-containing protein 1 (YTHDC1), a binding protein to m 6 A, in the development of type 2 diabetes (T2D). Methods: HPLC-MS/MS and qRT-PCR were used to quantify m 6 A and YTHDC1 levels in white blood cells from patients with T2D and healthy individuals. MIP-CreERT and tamoxifen treatment were used to create β-cell Ythdc1 knockout mice (βKO). m 6 A sequencing and RNA sequencing were performed in wildtype/βKO islets and MIN6 cells to identify the differential genes. Results: In T2D patients, both of m 6 A and YTHDC1 levels were reduced and associated with fasting glucose. Deletion of Ythdc1 resulted in glucose intolerance and diabetes due to decreased insulin secretion, even though β-cell mass in βKO mice was comparable to wildtype mice. Moreover, Ythdc1 was shown to bind to SRSF3 (serine/arginine-rich splicing factor 3) and CPSF6 (cleavage and polyadenylation specific factor 6) in β-cells. Conclusions: Our data suggested that YTHDC1 may regulate mRNA splicing and export by interacting with SRSF3 and CPSF6 to modulate glucose metabolism via regulating insulin secretion, implying YTHDC1 might be a novel potential target for lowing glucose.